Current management of the stability of organizations of the investment and construction complex in crisis situations - A. V. Kozlovsky; N. A. Moiseenko; O. E. Astafyeva (Управление)
The article сonsiders topical issues of managing the economic stability of organizations in a crisis. The authors substantiate the need to study regional trends as an integral part of the anticrisis program at the regional level. Early diagnosis of crisis phenomena in the economy proves that a sufficiently high level of socio-economic development does not yet ensure complete economic security and the ability to withstand the threats posed by the unbalanced structure of the economy. Based on this, the problems in the field of ensuring the stability of organizations in the conditions of crises have been analysed and generalized. The problems faced by enterprises and organizations of the investment and construction sector of the economy have been considered. In methodological terms, the authors propose to use a system of indicative analysis and regulation of production and economic activities of enterprises of the real sector of the economy, as an organizational tool for resolving crisis situations in the economy. The study justifies the necessity of the introduction of digital technologies, on the basis of which it is possible to quickly implement the tasks set and achieve the expected results. The authors emphasize that we need our own anticrisis programs that to help maintain the sustainable functioning of organizations in the conditions of crisis phenomena.